KOMPETENSI SOSIAL GURU DI MADRASAH ALIYAH DARUL QUR’AN KARIMAN PEKANBARU - Riska Awaliyah; Alya Zakiyah Jamel, Ade Irma, Rena Revita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to identify the social competence of teachers at Madrasah Aliyah Darul Qur'an Kariman and its impact on the learning environment. The study used a qualitative approach with observation and interview methods, which allowed researchers to capture teachers' social interactions directly with students, colleagues, and parents. The observation results show that teachers in this madrasah have good communication skills and high empathy, which creates a conducive classroom atmosphere and supports students' character development. In addition, cooperation among teachers is harmonious, which strengthens the positive working climate in the madrasah environment. Teachers also use a mediation approach in handling conflicts between students, and actively communicate with parents to support student development. Overall, teachers' social competence in this madrasah plays an important role in supporting a holistic learning process and students' overall development